PENERAPAN SANKSI PIDANA BAGI ORANG ASING PELAKU TINDAK PIDANA KEIMIGRASIAN ( SUATU STUDI DOKTRINAL) - Suryanto, Eddy (Wacana Hukum, 2010)
Abstract The frame of reference of this research is that by the regulation of criminal rule on the Constitution of No. 9, 1992 jo No 37,2009, on the immigration(abstract-condemnation), intended the rule to have a power of reinforcement to be obeyed. And towards those of domestic as well as foreigners breaking the law will be enforced to have criminal sanction when they were proved of legelly giuilty and convincincing without any reasons of truth and excuse and also able to be responsible for the judge( as a punisher of inconcrete criminal). It’s needed a judge’s consideration  based on the law, social, economic and other factors enfluecing law enforcement , to enforce the criminal law. ----The considerationsthe taken for the decision making  are acquired from the facts attended at the trial session and the facts clarified at the authentication step. Then, the facts are evaluated and corrected with  letter of accusation, demand, plea, counterplea, rejoinders found as a fact, so that the judge convinced that the accused did the criminal law of immigration. Key word: foreigners breaking the law